The Concept Of Arranging The Old Pekan Labuhan City Area As A Cultural And Historical Tourism Area - Rini Kustiah rini; Feby Milanie; Abdi Sugiarto (ISNU Sumatera Utara, 2024)
The Old City area of Pekan Labuhan in Medan, once the center of the Deli Sultanate (1728–1888), has lost its appeal due to poor environmental and cultural maintenance. The Deli River, once the city's lifeline, has also experienced physical, chemical, and biological degradation. The Medan city government plans to designate this area as a cultural and nature reserve under Regional Regulation No. 1 of 2022, focusing on preserving historical and cultural values to support history-based tourism and strengthen local identity. This study uses a qualitative descriptive method, combining field observations and literature reviews. Key issues identified include limited communal parking, poor pedestrian infrastructure, neglected buildings, and the conversion of historical structures. Solutions based on the Urban Heritage concept include creating visitor parking areas, vertical gardens, signage, riverbank open spaces, revitalizing Chinese heritage buildings, and improving pedestrian pathways. Nonphysical strategies involve engaging youth, fostering public-private partnerships, organizing annual events, promoting local products, and marketing the area through social media. In conclusion, zoning that integrates tourism with historical preservation is essential. By applying heritage principles and developing urban heritage tourism, the Old City can present its rich past as a modern attraction. This Urban Heritage Concept aims to serve as a model for managing heritage sites across Indonesia.